2014
DOI: 10.1111/nmo.12488
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and intrarater reliability of the Chicago Classification in pediatric high‐resolution esophageal manometry recordings

Abstract: Background The Chicago Classification (CC) facilitates interpretation of high‐resolution manometry (HRM) recordings. Application of this adult based algorithm to the pediatric population is unknown. We therefore assessed intra and interrater reliability of software‐based CC diagnosis in a pediatric cohort. Methods Thirty pediatric solid state HRM recordings (13M; mean age 12.1 ± 5.1 years) assessing 10 liquid swallows per patient were analyzed twice by 11 raters (six experts, five non‐experts). Software‐placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…This potential for incorrect diagnosis when applying the adult CC criteria to pediatric patients might strongly influence treatment choice. Studies have also shown that the interpretation of HRM is reproducible, but there are still some specific areas that may need more validation.…”
Section: Discussionmentioning
confidence: 99%
“…This potential for incorrect diagnosis when applying the adult CC criteria to pediatric patients might strongly influence treatment choice. Studies have also shown that the interpretation of HRM is reproducible, but there are still some specific areas that may need more validation.…”
Section: Discussionmentioning
confidence: 99%
“…The DL (s) was determined as the time from swallow onset (either through upper esophageal sphincter [UES] relaxation or the onset of impedance drop at the most proximal channel) to the CDP. 27 Pressure-flow analysis Data were exported as comma separated values and esophageal PFA was performed using MATLAB based automated software (Esophageal AIMplot software; T Omari © ; The MathWorks Inc, Natick, MA, USA). Five observer-determined regions of interest were used to guide analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The CFV (cm/s) was determined as the slope of the tangent approximating the 30 mmHg isocontour between the proximal transition zone and contractile deceleration point (CDP). The DL (s) was determined as the time from swallow onset (either through upper esophageal sphincter [UES] relaxation or the onset of impedance drop at the most proximal channel) to the CDP …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the available diagnostic criteria need to be adjusted for age and size, specifically the integrated relaxation pressure (IRP4) reflecting deglutitive EGJ relaxation and distal latency (3). Although the CC appears to be applicable for use in the general pediatric population (4, 5), its use in EA as a specific patient subgroup requires further consideration. EA patients often show no motor patterns, and therefore bolus transport to, and through, the EGJ needs to be considered.…”
Section: Current Diagnostic Methods To Investigate Dysphagia In Eamentioning
confidence: 99%